2015
DOI: 10.5152/iao.2015.1087
|View full text |Cite
|
Sign up to set email alerts
|

Normal Gain of VOR with Refixation Saccades in Patients with Unilateral Vestibulopathy

Abstract: OBJECTIVE:To characterize the response in the video head-impulse test for the assessment of the vestibulo-ocular reflex (VOR) in patients because of vertigo and dizziness. MATERIALS and METHODS:After rightward and leftward head impulses, the following results evaluated were: gain of the reflex and appearance of refixation saccades. A particular type of response (normal gain VOR and refixation saccades) was evaluated in a group of patients. RESULTS:In patients with a unilateral abnormality consisting of normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 21 publications
2
42
0
3
Order By: Relevance
“…This may result in alterations in vestibular function, characterized by reduced vestibulo-ocular reflex (VOR) gain and increased VOR gain variability with advancing age ( 1 , 2 , 8 ). Reduced function of the angular VOR results in generation of compensatory saccades ( 3 , 9 , 10 ). Studies have shown that compensatory saccades occur more frequently with increasing age ( 3 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may result in alterations in vestibular function, characterized by reduced vestibulo-ocular reflex (VOR) gain and increased VOR gain variability with advancing age ( 1 , 2 , 8 ). Reduced function of the angular VOR results in generation of compensatory saccades ( 3 , 9 , 10 ). Studies have shown that compensatory saccades occur more frequently with increasing age ( 3 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that compensatory saccades occur more frequently with increasing age ( 3 , 11 ). Interestingly, compensatory saccades have been observed in older individuals even when VOR gain was clinically in the normal range ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Instead, a compensatory quick eye movement toward the target, called refixation saccades, will occur ( 3 ). Recently, several studies reported that refixation saccades with normal gain values can occur in patients with unilateral vestibulopathy ( 11 , 20 , 21 ). However, the hand position was not described in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Refixation saccades with normal gain values have been reported to occur more frequently with increasing age (24). …”
Section: Discussionmentioning
confidence: 99%
“…Using vHIT, Perez-Fernandez and Eza-Nunez examined 623 patients with vertigo and dizziness (4). In the final population, he included patients with gain values > 0.8 with unilateral refixation saccades.…”
Section: Discussionmentioning
confidence: 99%